"Preleukemic or smoldering" chronic myelogenous leukemia (CML):BCR-ABL1 positive: A brief case report. Issue 1 (2015) - Bennett, John M.; Dsouza, Kevin G.; Patel, Mehul; O'Dwyer, Kristen
Abstract: Chronic myelogenous leukemia (CML), in the Chronic Phase (CP), is often suspected as a result of a complete blood count (CBC), which shows increased granulocytes, mostly mature including a peak in myelocytes, increased basophils, and rarely blasts and/or promyelocytes. Morphologic dysplasia is not present. CML is confirmed by detecting the characteristic Philadelphia chromosome (Ph)[t(9;22)(q34;q11.2)] by routine cytogenetics or fluorescent in situ hybridization (FISH) or molecular studies (RT-PCR) for the bcr-abl fusion gene. The most common feature of CML is an elevated WBC count, usually above 25×10 3 /µL, and frequently above 100×10 3 /µL. We report a case of confirmed Ph+CML with a normal CBC detected because of the presence of rare myelocytes and 2% basophils [Fig. 1 ]. Previous leukocyte counts for the preceding eight years were normal with the exception of one done four months prior to his presentation that showed an abnormal differential with 1% basophils, 2% metamyelocytes and 2% myelocytes. Highlights: A "normal" complete blood count does not rule out CML. The finding of metamyelocytes and or increased % of basophils warrants further assessment. If there are no other clinical explanations then a BCR-ABL transcript should be obtained from the peripheral blood. If negative proceed with a bone marrow aspirate and cytogenetics.